Structural dissection and high-throughput screening of mannosylglycerate synthase. - Flint, J; Taylor, E; Yang, M; Bolam, D; Tailford, L; Martinez-Fleites, C; Dodson, E; Davis, B; Gilbert, H; Davies, G (2005)
The enzymatic transfer of activated mannose yields mannosides in glycoconjugates and oligo- and polysaccharides. Yet, despite its biological necessity, the mechanism by which glycosyltransferases recognize mannose and catalyze its transfer to acceptor molecules is poorly understood. Here, we report broad high-throughput screening and kinetic analyses of both natural and synthetic substrates of Rhodothermus marinus mannosylglycerate synthase (MGS), which catalyzes the formation of the stress protectant 2-O-alpha-D-mannosyl glycerate. The sequence of MGS indicates that it is at the cusp of inverting and retaining transferases. The structures of apo MGS and complexes with donor and acceptor molecules, including GDP-mannose, combined with mutagenesis of the binding and catalytic sites, unveil the mannosyl transfer center. Nucleotide specificity is as important in GDP-D-mannose recognition as the nature of the donor sugar.